Survival Trends for Uterine Sarcomas from a Tertiary Center: The Oxford Experience - Aakriti Aggarwal; Federico Ferrari; Andreas Zouridis; Sean Kehoe; Sarah Pratap; Elisa Gozzini; Hooman Soleymani Majd (Diseases)
Uterine sarcomas are rare and aggressive gynecological malignancies. We evaluated the epidemiology, treatment outcomes and survival rates in uterine sarcoma patients managed in our institute. The medical records of women with histology proven uterine sarcoma, including leiomyosarcoma (LMS), adenosarcoma (ADS), and endometrial stromal sarcoma (ESS), treated at our institution from February 2010 to February 2022, were analyzed. In total, 41 patients were identified. In detail, LMS, ADS, and high-grade and low-grade ESS were identified, respectively, in 60.9%, 19.5%, 12.1%, and 7.3% of the cases. The majority of women affected by LMS (72%) underwent primary surgery and 40% of them also received adjuvant chemotherapy. A surgical approach was the preferred mode of treatment in 83% of the recurrences. The median OS (overall survival), DFS (disease free survival), and PFS (progression free survival) for the LMS group were 25, 44.5, and 8 months, respectively. The 5-year survival rates for LMS, ADS, and ESS groups were 30.5%, 100% and 37.5%, respectively. The 5-year survival for LMS was found to be significantly worse than for other histology types (p = 0.016). Our study provides valuable data for the evaluation of treatment strategies and survival trends among these rare cancers. The management and follow-up planning of each subtype requires a thorough patient-focused multidisciplinary discussion.